Childless Marriage in Indonesian Law: A Maqāṣid al-sharī‘ah Analysis of Ḥifẓ al-nasl - Ahmad Dahlan (Universitas Lampung, 2025)
Examines childless marriage in Indonesian law through a maqāṣid al-sharī‘ah [objectives of Islamic law] perspective, with particular attention to the interpretation of ḥifẓ al-nasl [protection of lineage]. It analyzes how Indonesian positive law and Islamic legal objectives conceptualize reproduction, lineage, and family obligations in the context of contemporary childlessness. Using a normative-juridical and conceptual approach, the study examines Indonesian marriage regulations, especially Law No. 1 of 1974 as amended by Law No. 16 of 2019, alongside classical and contemporary maqāṣid literature. The findings show that Indonesian positive law does not explicitly prohibit childless marriage, but implicitly regulates reproductive responsibility through norms concerning the purposes of marriage and family welfare. From a maqāṣid perspective, ḥifẓ al-nasl is not limited to an obligation to have children, but functions as a broader principle of preserving legitimate lineage and social continuity, allowing interpretive space for circumstances such as health, psychological, and socio-economic factors. This study argues that childless marriage constitutes a dynamic normative issue rather than a dichotomous conflict between Islamic law and state law, and contributes a nuanced maqāṣid-based framework for understanding childlessness within Indonesian family law and contemporary legal discourse.